Replacement of the TPS bending chamber with an on-site cutting method. (September 2017) - Chan, C.K.; Chang, C.C.; Shueh, C.; Yang, I.C.; Wu, L.H.; Cheng, C.M.; Huang, Y.T.; Chuang, J.Y.; Cheng, Y.T.; Hsiao, Y.M.; Chen, B.Y.; Sheng, Albert
Abstract: To minimize the impact on the machine downtime due to replacement of a TPS bending chamber, an on-site cutting method had been developed. This method can shorten the replacement time of a bending chamber from 50 to 4 days and avoid breaking the vacuum in the frond ends and adjacent insertion devices. We also developed a plug to prevent micro dust, generated from saw-cutting of the vacuum chamber, contaminating the beam duct. Three different preconditioning methods, including baking, prebaking and no-bake treatments, were applied to the newly installed arc-cell vacuum systems to evaluate their efficacy on reducing the photon stimulated desorption (PSD) in the vacuum chambers. The PSD data show no obvious discrepancy between these preconditioning methods. Highlights: An on-site cutting method which can dramatically shorten the replacement time of a bending chamber from 50 to 4 days was developed. A special plug which can prevent micro dust generated from saw-cutting of the vacuum chamber was developed. The photon stimulated desorption (PSD) data show no obvious discrepancy between these preconditioning methods: baking, prebaking and no-bake treatments.